PERANAN PROFITABILITAS DAN LIKUIDITAS DALAM MEMPENGARUHI RETURN SAHAM DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL PEMODERASI - Arsalan, Falih; Nursiam, Nursiam (LAND JOURNAL, 2024)
This study aims to explore how Profitability (ROA) and Liquidity (CR) affect Stock Returns, considering Dividend Policy as a moderating variable. The focus on the consumer sector was chosen due to its stable and defensive characteristics, even in uncertain economic conditions. The research sample includes companies listed on the Indonesia Stock Exchange (IDX) during the period 2020-2022, totaling 56 companies after handling outliers. Data analysis employs Multiple Linear Regression and Moderation Regression Analysis using SPSS version 25. The results indicate that Liquidity significantly influences Stock Returns, while Profitability does not show a significant impact. DPR, while not moderating the effect of Profitability on Stock Returns, can strengthen the relationship between Liquidity and Stock Returns in the context of consumer sector companies.